The Analysis of the Ability NaOH Activated Rice Husk Ash Silica to Reduce Cl Ion Levels - Febryzha, Nurul Widya; Harimu, La; Mulyana, Wa Ode; Mandasari, Ekacahyana (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Research has been carried out to analyze the ability of NaOH-activated rice husk Ash Silica to reduce Cl Ion Levels. This study aimed to determine the optimum mass, optimum pH, optimum contact time and apply NaOH-activated rice husk ash silica to reduce Cl ion levels in seawater. The method used in this study was an experimental method with the parameters studied, namely optimum mass, optimum pH, optimum contact time, and the ability of NaOH-activated rice husk ash silica to reduce Cl ion levels in seawater. The results showed that the optimum adsorbed percentage of Cl ions occurred at an optimum mass of 0.025 gram, optimum pH of 7, and optimum contact time of 30 minutes with an adsorbed percentage of 45.7% and an adsorption capacity of 9.14 mg/g. The Cl ion content of seawater samples that can be reduced using NaOH-activated rice husk ash silica is 16.925 ppm with an adsorbed percentage of 33.85%, so it can be concluded that NaOH-activated rice husk ash silica can be used to reduce Cl ion levels.